2018
DOI: 10.1213/ane.0000000000002852
|View full text |Cite
|
Sign up to set email alerts
|

Patients at High Risk for Obstructive Sleep Apnea Are at Increased Risk for Atrial Fibrillation After Cardiac Surgery: A Cohort Analysis

Abstract: Increasing risk for OSA, assessed by STOP-BANG, was associated with higher odds of postoperative atrial fibrillation, but not prolonged duration of mechanical ventilation or ICU length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
2
15
1
Order By: Relevance
“…The incidence of POAF ranged from 8% to 67% in the patients with SDB and from 6% to 42% in the patients without SDB. The definition of atrial fibrillation was mostly based on findings from continuous electrocardiographic monitoring and electrocardiographic examination, while eight studies did not supply such information [ 20–21 , 23 , 26 , 29 , 31 , 36 , 39 ]. The most common surgery type was CABG, and eleven studies included other surgery types such as valve replacement [ 21 , 27 , 30–31 , 33–35 , 37–39 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of POAF ranged from 8% to 67% in the patients with SDB and from 6% to 42% in the patients without SDB. The definition of atrial fibrillation was mostly based on findings from continuous electrocardiographic monitoring and electrocardiographic examination, while eight studies did not supply such information [ 20–21 , 23 , 26 , 29 , 31 , 36 , 39 ]. The most common surgery type was CABG, and eleven studies included other surgery types such as valve replacement [ 21 , 27 , 30–31 , 33–35 , 37–39 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“… 8 Other studies showed an increased risk of postoperative atrial fibrillation following cardiac surgery in patients with OSA. 9 , 30 However, these previous studies were most cross‐sectional, retrospective or prospective cohort studies, 8 and cannot overcome the influence of unmeasured confounders due to the nature of observational study. The present study found a causal effect of genetically predicted OSA on risk of atrial fibrillation using MR methods, which may control unmeasured confounders and reverse causation.…”
Section: Discussionmentioning
confidence: 99%
“…81 Obstructive sleep apnea has been associated with many poor postoperative outcomes, including major adverse cardiac events, 82,83 reduced ejection fraction, 81 and especially postoperative atrial fibrillation. [83][84][85] Patients with OSA also tend to stay in the intensive care unit and hospital longer as well as present for readmission more often compared to patients without sleep apnea. 84,86 Patients with OSA may also require permanent pacemaker placement more frequently after valve surgery.…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%